Respostas

  • Usuário do Brainly
2013-02-18T12:42:59-03:00

a)

 

Temos que:

 

\text{P}(\text{x})=2\text{x}^4-\text{x}^3+\text{x}^2+\text{x}+3

 

\text{Q}(\text{x})=\text{x}^3+2\text{x}^2-\text{x}+3

 

Desta maneira, podemos afirmar que:

 

\text{P}(\text{x})+\text{Q}(\text{x})=(2\text{x}^4-\text{x}^3+\text{x}^2+\text{x}+3)+(\text{x}^3+2\text{x}^2-\text{x}+3)

 

\text{P}(\text{x})+\text{Q}(\text{x})=2\text{x}^4+3\text{x}^2+6

 

 

b)

 

\text{P}(\text{x})-\text{Q}(\text{x})=(2\text{x}^4-\text{x}^3+\text{x}^2+\text{x}+3)-(\text{x}^3+2\text{x}^2-\text{x}+3)

 

\text{P}(\text{x})-\text{Q}(\text{x})=2\text{x}^4-\text{x}^2+2\text{x}

 

 

c)

 

\text{Q}(\text{x})-\text{P}(\text{x})=(\text{x}^3+2\text{x}^2-\text{x}+3)-(2\text{x}^4-\text{x}^3+\text{x}^2+\text{x}+3)

 

\text{Q}(\text{x})-\text{P}(\text{x})=-2\text{x}^4+2\text{x}^3+\text{x}^2-2\text{x}

1 5 1